P208 Abnormal coronary flow reserve assessed with stress echocardiography induces a reduction in transmural strain gradient and an increase in heterogeneous myocardial electrical activation. (17th January 2020) - Sierra Lara M, J D; Rodriguez-Zanella, H; Calvillo, O; Posada, E L; Ortiz, X O; Arroyo, C; Raymundo, G; Ruiz Esparza, M E; Fritche, J F; Wierzbowska-Drabik, K; Gaibazzi, N; Picano, E; et al.
Abstract: OnBehalf: Echo Lab INC Background: The integrated quadruple stress echo (IQ-SE) is a state-of-the-art protocol that expands the risk stratification potential of SE. The coronary flow reserve (CFVR) has pronostic implication mainly in the absence of wall motion abnormalities. Longitudinal multilayer strain analysis assesses trasmural strain gradient. The prognostic value of multilayer strain analysis alongside the IQ-SE has not been established. We aim to determine the additive value of multilayer strain analysis during IQ-SE. Methods: Prospective observational study. We evaluated one hundred twenty intermediate-high risk patients without obstructive coronary artery disease (mean age 61 ± 12 years, female 43%) with IQ-SE dipyridamole at our institution. Abnormal CFVR was defined as CFVR <2. Multilayer strain analysis and mechanical dispersion, were performed during rest and stress, with an automatic frame-by-frame with speckle tracking. Results: The IQ-SE was feasible in all patients. At rest, mean three-dimensional left ventricular ejection fraction (3D LVEF) was 59% (53-62) without wall motion abnormalities. Abnormal CFVR was seen in 38 patients (32%) and reduced left ventricular contractile reserve (LVCR) in 56 patients (46%). Patients with abnormal CFVR, showed a reduction in EndoLS and transmural strain gradient, and an increase in mechanical dispersion and in lung B-lines during stress. No differences were observed in 3D LVEF and LVCR. Conclusions: Endocardial ischemia due to microvascular dysfunction leads to a reduction in transmural strain gradient. Adding multilayer strain analysis to IQ-SE might detect myocardial subclinical dysfunction, arrhythmic risk and pulmonary congestion due to microvascular dysfunction.